Radiological Evaluation of Postsurgical Course of Perforators in Retrograde Posterior Tibial Fasciocutaneous Flaps for Distal Leg and Foot Defects - Agrawal, Neeraj Kant; Bhattacharya, Visweswar; Dubepuria, Rahul (Indian Journal of Plastic Surgery, 2021)
Background Mapping of vascular perforators by various methodologies have been described for planning of a variety of flaps in the lower limbs. We attempted to assess the changes in posterior tibial perforators after transfer of fasciocutaneous flaps for leg defects.Methods 20 patients with distal leg and foot defects were studied by computed tomography angiography (CTA) and preoperative audio Doppler to ascertain perforators of posterior tibial artery. Fasciocutaneous flaps were raised, based on these perforators, depending on the site and size of soft-tissue defects. The number of perforators and their distance from the medial malleolus were also studied. Postoperative CTA was performed on the 7th to 10th day, with emphasis on postoperative changes of the perforators on which the flaps were based.Results One to four posterior tibial perforators were found between 5 cm and 8 cm proximal to the medial malleolus. After flap transfer, the perforators could be traced to variable distance through the total length of the flap. The perforators formed small vascular loop in 12 patients, following retrograde posterior tibial flap transfer. The height of the loop, the number of such loops, the dilatation and tortuosity of the perforators, and their longitudinal orientation were studied in detail. Most of the findings can be explained by mechanical realignment of perforators as well as by the delay phenomenon associated with retrograde fasciocutaneous flaps.Conclusion It was concluded that the morphological changes associated with the perforators explained the vascular rationality and success of these flaps.
Keywords: posterior tibial perforators; fasciocutaneous flaps; pedicled flaps; perforator assessment; CTA; vascular mapping